2016
DOI: 10.1002/prca.201500075
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and glomerulonephritis: A complementary approach in renal pathology for the identification of chronic kidney disease related markers

Abstract: Glomerulonephritis (GN) is one of the most common origins of chronic kidney disease and its careful evaluation is crucial for prognostic and therapeutic purposes, with the renal biopsy still playing a central role for the diagnosis. However, due to its invasiveness, it is not devoid of complications and many investigations have focused on identifying biomarkers for chronic kidney diseases using less-invasive and easy-to-collect samples, such as urine and blood. In this context, proteomics has played a crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…One branch of pathology that may benefit most from the application of high spatial resolution MALDI‐MSI is renal pathology given the high complexity and heterogeneity associated with glomerular diseases . Membranous nephropathy (MN) represents one of the most pressing fields of application given that this glomerulopathy represents the most frequent cause of nephrotic syndrome in adults and approximately one‐third of patients progress to end stage renal disease (ESRD) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One branch of pathology that may benefit most from the application of high spatial resolution MALDI‐MSI is renal pathology given the high complexity and heterogeneity associated with glomerular diseases . Membranous nephropathy (MN) represents one of the most pressing fields of application given that this glomerulopathy represents the most frequent cause of nephrotic syndrome in adults and approximately one‐third of patients progress to end stage renal disease (ESRD) .…”
Section: Introductionmentioning
confidence: 99%
“…One branch of pathology that may benefit most from the application of high spatial resolution MALDI-MSI is renal pathology given the high complexity and heterogeneity associated with glomerular diseases. [13] Membranous nephropathy (MN) represents one of the most pressing fields of application [14] given that this glomerulopathy represents the most frequent cause of nephrotic syndrome in adults and approximately one-third of patients progress to end stage renal disease (ESRD). [15] Furthermore, there still remains a fair degree of heterogeneity in terms of patient response and outcomes following the administration of immunosuppressive treatment [16] and a marker that can reliably predict the response of a patient to this therapeutic treatment a priori is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic approaches have revealed differences in protein expression among many different glomerular diseases [70]. In addition, Rocchetti et al [71] showed that low urinary levels of kininogen could discriminate between patients with IgA nephropathy, responders or non-responders to therapy with angiotensin-converting enzyme inhibitors.…”
Section: Glomerulonephritismentioning
confidence: 99%
“…To this end, the introduction of proteomic analysis to the field of pathology has represented a significant step forward in the study of disease at clinical and experimental levels, and in the search of biomarkers (Figure 1F) (see for example [42,43,44,45,46,47]). This methodological platform offers complementary and often advantageous outcomes as compared to other methods mentioned above.…”
Section: Extracellular Matrix Pathology: An Elusive Aspect In the mentioning
confidence: 99%